2017
DOI: 10.1002/ijc.30591
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutation coupled with p53 loss is sufficient to induce ovarian carcinosarcomas in mice

Abstract: Ovarian carcinosarcoma cancer is the most lethal form of gynecological malignancy, but the pathogenesis and biological function for this ovarian cancer remain unknown. We establishment the transgenic mouse model of K-ras p53 and found that K-ras mutation and p53 deletion within the ovarian surface epithelium gave rise to ovarian lesions with a hyperproliferation and endometrioid glandular morphology. Furthermore, double mutant ovaries formed ovarian carcinosarcomas that were high grade and poorly differentiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…RAS‐ERK and RAS‐AKT signaling transmit signals from a vast variety of inputs to support cancer proliferation, survival and metastasis . P53 is a well‐known tumor suppressor and acts as guardian of the genome for promoting cell cycle arrest, apoptosis, senescence and DNA repair . The P53 pathway is frequently inactivated in many cancers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RAS‐ERK and RAS‐AKT signaling transmit signals from a vast variety of inputs to support cancer proliferation, survival and metastasis . P53 is a well‐known tumor suppressor and acts as guardian of the genome for promoting cell cycle arrest, apoptosis, senescence and DNA repair . The P53 pathway is frequently inactivated in many cancers.…”
Section: Resultsmentioning
confidence: 99%
“…12 P53 is a well-known tumor suppressor and acts as guardian of the genome for promoting cell cycle arrest, apoptosis, senescence and DNA repair. 13,14 The P53 pathway is frequently inactivated in many cancers. Hypoxia is a central characteristic during cancer development and regulates angiogenesis, cell survival, proliferation, apoptosis, adhesion and metabolism.…”
Section: Aging Widely Impacts Specific Pathways Across Cancersmentioning
confidence: 99%
“…Animal models have shown that endometriosis‐like lesions can be induced in mice by activation of KRAS or deletion of PTEN, and a combination of these abnormalities, such as KRAS activation plus TP53 loss, concurrent inactivation of TP53 and Rb1, PTEN loss plus PIK3CA activation, and KRAS activation plus PTEN loss leads to the development of malignant ovarian tumors that resemble endometrial cancer in humans. Thus, these data seem to suggest that more than one driver mutation is needed for malignant transformation.…”
Section: Changing Pressure For Genomic Alteration Due To Oxidative Stmentioning
confidence: 99%
“…A recent study demonstrated that conditional deletion of p53 coupled with the activating K-ras mutation led to development of endometrioid ovarian carcinosarcomas. 90 In addition, the combined mutations resulted in simple endometrioid glandular morphology and peritoneal endometriotic lesions as early as 4 weeks after AdCre injection through the ovarian, 90 indicating that TP53 loss, in conjunction with KRAS activation, may transform OMA into malignancy.…”
Section: Tp53mentioning
confidence: 99%
“…The combinatorial effect of mutations of both genes in the ovary resulted in endometrioid ovarian adenocarcinomas [153]. In a transgenic mouse model of OC, malignant transformation in endometriosis with mutation of Kras and p53 deletion within the ovarian surface epithelium showed hyperproliferative endometrioid glandular morphology [154]. Endometrial endometroid cancer (EEC) may be developed in a mouse model by the concurrent involvement of loss of function in PTEN, gain of function of PI3K and CTNNB1 [155].…”
Section: Oncogenes and Tumor Suppressor Genesmentioning
confidence: 99%